2013
DOI: 10.1111/echo.12117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Increase in Left Ventricular Pressure Overload on Left Atrial‐Left Ventricular Coupling in Patients with Hypertension: A Two‐Dimensional Speckle Tracking Echocardiographic Study

Abstract: In patients with hypertension, an elevation in SBP leads to increased LA stiffness during ventricular systole and LV diastolic stiffness, in association with continued and further advanced LV diastolic dysfunction. 2DSTE is considered a sensitive tool for detecting abnormal LA-LV coupling related to an increased LV pressure overload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 28 publications
4
30
1
Order By: Relevance
“…However, in clinical practice, we do not routinely assess the different components of LA function, although this is now possible because of advances in noninvasive imaging techniques. Recent studies based on tissue Doppler imaging [9], vector velocity imaging (VVI) [10,11], or speckle tracking imaging (STE) [12][13][14][15][16] assessed LA function in patients with HTN with or without LV hypertrophy. However, literature data concerning LA strains in patients with HTN are conflicting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in clinical practice, we do not routinely assess the different components of LA function, although this is now possible because of advances in noninvasive imaging techniques. Recent studies based on tissue Doppler imaging [9], vector velocity imaging (VVI) [10,11], or speckle tracking imaging (STE) [12][13][14][15][16] assessed LA function in patients with HTN with or without LV hypertrophy. However, literature data concerning LA strains in patients with HTN are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…However, literature data concerning LA strains in patients with HTN are conflicting. Left atrial reservoir function has been shown to be reduced [12,13] or normal in patients with LV hypertrophy [10,11], whereas it showed early impairment in some studies of HTN patients without hypertrophy [14][15][16]. LA conduit function has been more consistently shown to be reduced, regardless of LV mass [9][10][11]13,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Each cardiomyopathy disease(hypertrophic [68,75], restrictive [76,77], dilated [78], ischemic [79,80], hypertensive [81,82], arrhythmogenic right ventricular [83], myocarditis [84], left ventricular non-compaction [85,86]) each has validated pathophysiologic features that can confirm a risk state [52,87]. Averaged features have a very low incidence of false positives and false negatives results [9,14,48,50].…”
Section: Cardiomyopathiesmentioning
confidence: 99%
“…The essential pathophysiologic data used to depict the risk of hypertensive heart disease [81,82] and "pseudo-HCM" [48, 91,92] are identical to those of general cardiomyopathies [60] Table 1&2. Screening blood pressure and increased LVwall thickness serve only as benchmarks that require physiologic classification as normal compensatory physiology versus emergent heart disease [91].…”
Section: Hypertensive Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation